Consider the following depiction:

enter image description here

$ABC$ is an isosceles triangle ($AB=AC$), where the two angles opposite the equal sides are equal $\beta$ ($\beta>60$), and $AD$ perpendicular to $BC$.

$O$ is the center of the circumscribed circle of $ABC$, and $M$ is the center of the incircle of $ABC$.

I want to express the area of the triangle $BOM$ and the radius of the incircle of $ABC$, in terms of $k$ and $\beta$.

This is what I tried: I denoted the radius of the circumscribed circle as $R$, and the radius of the incircle as $r$.
The area of $BOM$ can be obtained by: $\frac{k\cdot BD}{2}$, and $BD=\frac{BC}{2}$, I get that the area is actually: $\frac{k\cdot BC}{4}$.
Now from Law of sines I get $BC=\sin(180-2\beta)\cdot 2 R$.
So this reduces to problem to expressing $R$ (which is $OA$) in terms of $\beta$ and $k$. This is where I'm stuck. I couldn't find a way to do that.
I know that $OA=OB=R$, and that $AOB$ is also isosceles triangle, and I have a feeling it is important, but I can't figure out what am I missing...
Hints and guidelines would be very appreciated.


Assuming $BD=1$, we have $AB=AC=\frac{1}{\cos\beta}$, $[ABC]=\tan\beta$, $$ R = \frac{AB}{2\sin\beta} = \frac{1}{\sin(2\beta)}$$ and: $$ r = \frac{2[ABC]}{AB+AC+BC} = \frac{\tan\beta}{1+\frac{1}{\cos\beta}}=\frac{\sin\beta}{1+\cos\beta}=\tan\frac{\beta}{2}. $$ Moreover, by Euler's theorem we have: $$ k^2 = OM^2 = R^2-2Rr = \frac{1}{4\sin^2\beta\cos^2\beta}-\frac{1}{\cos\beta(1+\cos\beta)} $$ so: $$ k^2 = \frac{(1-2\cos\beta)^2}{4\cos^2\beta(1-\cos^2\beta)} $$ and: $$ k = \frac{1-2\cos\beta}{\sin(2\beta)}. $$ This gives, in general, $$ BD = \frac{\sin(2\beta)}{1-2\cos\beta} k, $$ so: $$ [BOM]=\frac{k}{2}BD = \frac{\sin\beta\cos\beta}{1-2\cos\beta} k^2,\tag{1} $$ and: $$ r = \frac{\sin\beta}{1+\cos\beta} BD = \frac{2(1-\cos\beta)\cos\beta}{1-2\cos\beta} k.\tag{2}$$



Let the equal sides be $x$,

Distance of circumcenter from A, OA = circumradius, $R=\dfrac{abc}{4\triangle}$

Distance of incenter from A, MA = $r\csc{\dfrac{A}{2}}$

You will get MA - OA in terms of $x$ and $\beta$, but MA - OA = k

Then you can substitute the value of $x$ in terms of $k$ and $\beta$ in the formula for the area, i.e.

$\dfrac{1}{2}\cdot2x\cos\beta\cdot x\sin\beta$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.